(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Internal communication networks in student organizations play an important role in supporting the effectiveness of work program implementation. This study aims to analyze the communication network patterns of the Trunojoyo Art Festival (TAF) 2025 committee organized by the Nanggala Arts Student Activity Unit (UKM Seni Nanggala) of Trunojoyo University, Madura. The study uses a Social Network Analysis approach with a sociometric method to map communication relationships between committee members. Data were analyzed using UCINET VI software with a focus on network centrality measures, including degree centrality and graph centralization levels. The results show that the TAF 2025 committee communication network forms a centralized pattern with a centralization level of 68.40 percent. Actors with the initials DP as the chairperson and DW as the executive secretary are the main centers of information flow with the highest degree centrality values, respectively 1.000 and 0.923. The coordinator of each section acts as a liaison between the core committee and division members. Although the communication structure tends to be hierarchical, the success of the activity is still achieved through regular briefings, open communication in WhatsApp groups, and a responsive coordination culture